(untitled) (Gestión y Gerencia, 2018)
The University Council of the Centroccidental "Lisandro Alvarado" University (UC-UCLA) on 27-07-2011 approved the request of the Scientific Humanistic and Technological Development Council (CDCHT) for the creation of the "Lisandro Alvarado" Stimulus to Research Program (PEILA). It was implemented as of 2012. During these five years this Program has recognized the work of UCLA’s researchers. The PEILA, based on exclusively academic criteria, classifies researchers into three levels, which receive resources to support their research activity. Accredited researchers are recognized annually for their publications with an additional bonus for them. The program started with 249 accredited researchers in seven areas of knowledge and by 2016 were 161 registered and although level I decreased 43%, levels II and III increased 19 and 3% respectively. The results for the period 2012-2016 show that, despite the budget crisis, the PEILA has been consolidated as an instrument for institutional recognition and stimulation of university research at UCLA